ANALISIS BEBAN PENCEMARAN DAN KAPASITAS ASIMILASI DANAU SENTANI, PAPUA SEBAGAIUPAYAKONSERVASI LINGKUNGAN PERAIRAN - Auldry F Walukow; D Djokosetiyanto; KholiPdan KholiPdan; Dedi Soedharma (Research Center for Biology-Indonesian Institute of Sciences, 2008)
The Lake Sentani has problems. Firstly, high of erosion number i.e. 94.52 ton/ha/year of which the value is higher than erosion tolerance at average 25 ton/ha/year.Secondly, high concentration of chemical pollution such as Cu (0.0201- 0.1081 mg/L) and Zn (0.21 - 0.36 mg/L) which these values are above water quality standard approved by the government as ruled in PP 82 Tahun 2001 about the management of water quality and water pollution. Therefore research and management are needed to find solution for the sustainability of this lake. The aims of this research is to be acquainted with carrying capacity of Lake Sentani through analyzing 1) the pollution load, and 2) the assimilation capacity of Lake Sentani aquaculture. The collected information is important for future aquaculture environmental management and conservation. Result shows that the pollution loads from river are obtained as follows (ton/month): TDS (441.806 to 775.287), BOD (3.510 to 7.801) and COD (7.737 to 16.055).The assimilation capacities from lake are obtained as follows (ton/month): TDS (12.18494), BOD (11.31973) and COD (122.4184).The number of pollution loads (TDS, BOD and COD) are under the assimilation capacity.